2020
DOI: 10.1002/aelm.202000535
|View full text |Cite
|
Sign up to set email alerts
|

Growing Perovskite Quantum Dots on Carbon Nanotubes for Neuromorphic Optoelectronic Computing

Abstract: Brain‐inspired (neuromorphic) computing that offers lower energy consumption and parallelism (simultaneous processing and memorizing) compared to von Neumann computing provides excellent opportunities in many computational tasks ranging from image recognition to speech processing. To accomplish neuromorphic computing, highly efficient optoelectronic synapses, which can be the building blocks of optoelectronic neuromorphic computers, are necessary. Currently, carbon nanotubes (CNTs), an attractive candidate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 38 publications
(39 reference statements)
0
37
0
Order By: Relevance
“…[9,10,14] As illustrated in Figure 2d, Crawford et al fabricated a photonic synaptic device based on organic-inorganic halide perovskite QDs (PQDs) and multiwall carbon nanotube (MWCNT), which demonstrated the long-term potentiation under the 405 nm all-optical stimuli and the longterm depression with the consecutive À1 V/100 ms electrical pulses. [63] After that, they weakened the connection strength with higher efficiency by increasing the pulse width of electrical pulses, which indicated that it was feasible to adjust the learning process of neuromorphic computing by modulating various parameters of pulses. [63] For STP and LTP measurement of a single biomimetic synaptic device, the external stimuli are usually applied onto one terminal (the presynaptic terminal or the postsynaptic terminal).…”
Section: Biomimetic Synaptic Behaviors Of the Synaptic Devicementioning
confidence: 99%
“…[9,10,14] As illustrated in Figure 2d, Crawford et al fabricated a photonic synaptic device based on organic-inorganic halide perovskite QDs (PQDs) and multiwall carbon nanotube (MWCNT), which demonstrated the long-term potentiation under the 405 nm all-optical stimuli and the longterm depression with the consecutive À1 V/100 ms electrical pulses. [63] After that, they weakened the connection strength with higher efficiency by increasing the pulse width of electrical pulses, which indicated that it was feasible to adjust the learning process of neuromorphic computing by modulating various parameters of pulses. [63] For STP and LTP measurement of a single biomimetic synaptic device, the external stimuli are usually applied onto one terminal (the presynaptic terminal or the postsynaptic terminal).…”
Section: Biomimetic Synaptic Behaviors Of the Synaptic Devicementioning
confidence: 99%
“…Integrating the perovskite with organic semiconductors not only improves the photosensitivity of the system but it is also suitable to the solution-processed method instead of complex multistep processes in most previous works (Table S1). ,,, This hybrid phototransistor achieves better performance than most previous perovskite-based hybrid synaptic phototransistors including a photoresponsivity ( R ) of 4000 A/W and an excellent specific detectivity ( D *) of 2.8 × 10 16 Jones (Table S1). On basis of a type II band alignment heterojunction, it can be used to mimic the biological synaptic functions.…”
Section: Introductionmentioning
confidence: 93%
“…As already discussed, 0D essentially can not only build up components of artificial optoelectronic synaptic devices but can also integrate other types of materials such as, polymers, [265] nanowires, [98] and even QDs themselves into the optoelectronic synaptic devices. [244] Thus, in order to enhance the performance of current low-dimensional optoelectronic synapses, it is necessary to develop hybrid devices that are combined with 0D and 2D materials.…”
Section: Hybridly Built On 0d and 2d Materialsmentioning
confidence: 99%
“…[ 97 ] In addition, the inhibited recombination causes the photocurrent to decrease slowly, then originates the synaptic plasticity. [ 98 ] Photogenerated electron‐hole pairs may be separated via interfacial band alignment by using p‐n or Schottky junctions for the built‐in electrical field that can be created by doping or simply by combining hybrid materials. [ 99 ] In recent years, exploiting heterostructure to modulate the optoelectronic properties of materials has emerged as a new research area.…”
Section: Principles and Materials For Optoelectronic Synaptic Devicesmentioning
confidence: 99%
See 1 more Smart Citation